SYNTHESIS OF DENTAL FLUOROAPATITE GLASS-CERAMIC GLAZES - G. Aabolfathi; B. Eftekhari Yekta (Ceramics-Silikáty, 2011)
A dental glass-ceramic glaze based on the SiO2–Li2O3–P2O5–CaO system, which is currently used as dentin for lithiumdisilicate glass-ceramic cores, was synthesized. The role of Na2O, CaO and P2O5 in sintering and crystallization of the related glasses were studied by firing at temperatures higher than their dilatometric softening point. Sintering of glasses led to precipitation of needle - like fluoroapatite crystalline particles. However, in spite of current definition about glassceramics, the final synthesized composition and a similar trade mark sample, which was used as reference, did not show considerable amounts of crystalline phases after sintering process. Furthermore, reducing the constituent‘s of fluoroapatite in glass composition led to reduction of sinterability and fusibility of the system.